PENGARUH MODAL, PENGGUNAAN INFORMASI AKUNTANSI DAN KARAKTERISTIK WIRAUSAHA TERHADAP KEBERHASILAN USAHA MIKRO KECIL DAN MENENGAH DI DESA MENDALO INDAH - Hendi Gepsy; Wijaya, Rico; Olimsar, Fredy (Jambi Accounting Review (JAR), 2025)
This study aims to determine the influence of capital, the use of accounting information, and entrepreneurial characteristics on the success of micro, small, and medium enterprises in Mendalo Indah Village. The type of data used by the researcher is primary data. The research method uses a quantitative approach with a questionnaire used as the data collection method. The population in this study were micro, small, and medium enterprises in the Mendalo Indah Village area. The sampling method used proportional stratified random sampling with a final sample of 66 business units. Data testing techniques used validity and reliability tests, classical assumption tests, and hypothesis tests using SPSS v.27 software. The results of the study indicate that capital, accounting information, and entrepreneurial characteristics simultaneously influence business success. Capital and entrepreneurial characteristics partially influence business success. Accounting information partially does not influence business success.